Approximation by rational functions on doubly connected domains in weighted generalized grand Smirnov classes - Testici, A. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.5 Let GC be a doubly connected domain bounded by two rectifiable Carleson curves. In this work, we use the higher modulus of smoothness in order to investigate the approximation properties of (p-ε)-Faber–Laurent rational functions in the subclass of weighted generalized grand Smirnov classes E^p),θ ( G,ω ) of analytic functions.